2019
DOI: 10.1021/acs.jpcc.9b09635
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Stability of Ammonium Azide Under High Pressure

Abstract: Due to its potential applications as a high-energy density material, the high-pressure polymorphs of ammonium azide (AA) have received much attention recently. However, the crystal structure of phase Ⅱ (AA-II), stable above 3.0 GPa, has remained elusive until now. By combining X-ray diffraction and Raman experiments with first principle calculations, we determine that AA-II is a hydrogen(H)-bonded structure of ammonium and azide ions with monoclinic symmetry, space group P2/c. The latter is comprised of altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 33 publications
3
8
0
Order By: Relevance
“…We first investigated AA embedded in N compressed up to 30 GPa at room temperature using Raman spectroscopy. We observed no sign of phase transition in the Raman spectrum, the latter being consistent with previous measurements on pure AA and AA embedded in argon [ 12 , 14 ]. We then prepared three samples at pressures of about 15 GPa, 20 GPa, and 30 GPa, and studied them as a function of temperature in the range 300–700 K. The followed P – T paths are illustrated in Figure S2 of the SI.…”
Section: Materials and Methodssupporting
confidence: 92%
See 4 more Smart Citations
“…We first investigated AA embedded in N compressed up to 30 GPa at room temperature using Raman spectroscopy. We observed no sign of phase transition in the Raman spectrum, the latter being consistent with previous measurements on pure AA and AA embedded in argon [ 12 , 14 ]. We then prepared three samples at pressures of about 15 GPa, 20 GPa, and 30 GPa, and studied them as a function of temperature in the range 300–700 K. The followed P – T paths are illustrated in Figure S2 of the SI.…”
Section: Materials and Methodssupporting
confidence: 92%
“…A membrane diamond anvil cell (MDAC) was used to generate high pressures [ 19 ], equipped with diamond anvils of culet size of 300 m. Re gaskets of initial thickness of 200 m were preindented to a thickness of 35 m, and a hole of diameter of 95 m was laser-drilled at the center of the indent in order to serve as the sample chamber. A piece of AA sample of lateral size 40 to 50 m was loaded in the gasket hole and embedded in N by cryogenic loading of N , in the same fashion as our previous study using liquid argon [ 14 ]. The Raman spectrum of the AA sample after loading was compared to those that were measured in our previous study [ 14 ] and confirmed the absence of impurities, as shown in Figure S1 of the Supporting Information file (SI).…”
Section: Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations